Necessidade de informação de técnicos do Instituto Brasileiro de Geografia e Estatística - Sá, Regina de Almeida (1985)
IBGE social scientist's needs of information, for the performance of their work concerned with information for planning, are studied on the basis of data gathered through individual interviews, structured by questionnaire in which the critical incident technique was employed. The main sources of information for these social scientists consist of statistical data and related documents, besides books and periodicals, Portuguese and English being their principal languages. Accessibility and operational flow are the principal factors influencing use of information sources. The institution's library is used, through intermediaries, when there are informational needs other than statistical data collected by IBGE under the responsibility of the users themselves and available in their place of work. The users consider as good the library's services, although it is believed they do not know very well its collection. The results indicate the need for reformulation of the library´s dissemination policy concerning its users.